Uncertainties estimation in identification of digital planar surface parameters using a 3D laser sensor. (2018) - Barki, Mohamed; Asma, Farid
In modern metrological applications, 3D laser sensors are used to measure surface parameters. However, the performance of 3D laser sensor is influenced by its position and orientation angles on the target, which causes uncertainties in the measured parameters. In this paper, the influence of the position and orientation of a 3D laser plane sensor is studied by determining the measurement uncertainties on the parameters of a flat surface. Relative position and two orientation angles between the sensor and the surface are taken as the main characteristics of the sensor and are considered separately. In order to determine the uncertainties in the measurements, a set of measurements are performed on a reference part by using a coordinate measuring machine (CMM) equipped with a laser plane sensor.